2013
DOI: 10.1016/j.molcel.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

R Loops Are Linked to Histone H3 S10 Phosphorylation and Chromatin Condensation

Abstract: R loops are transcription byproducts that constitute a threat to genome integrity. Here we show that R loops are tightly linked to histone H3 S10 phosphorylation (H3S10P), a mark of chromatin condensation. Chromatin immunoprecipitation (ChIP)-on-chip (ChIP-chip) analyses reveal H3S10P accumulation at centromeres, pericentromeric chromatin, and a large number of active open reading frames (ORFs) in R-loop-accumulating yeast cells, better observed in G1. Histone H3S10 plays a key role in maintaining genome stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
219
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(230 citation statements)
references
References 43 publications
11
219
0
Order By: Relevance
“…DNA:RNA hybrid formation was shown to induce H3S10 phosphorylation (H3S10P) (Castellano-Pozo et al 2013), a chromatin mark that reduces HP1 binding to H3K9 methylated nucleosomes and interferes with heterochromatin formation and silencing (Fischle et al 2005;Kloc et al 2008). We determined H3S10P levels; however, we observed reduction of H3S10P in caf1Δdcr1Δ cells at tlh (Supplemental Fig.…”
Section: Absence Of Rna Degradation Leads To Changes In Chromatin Orgmentioning
confidence: 93%
“…DNA:RNA hybrid formation was shown to induce H3S10 phosphorylation (H3S10P) (Castellano-Pozo et al 2013), a chromatin mark that reduces HP1 binding to H3K9 methylated nucleosomes and interferes with heterochromatin formation and silencing (Fischle et al 2005;Kloc et al 2008). We determined H3S10P levels; however, we observed reduction of H3S10P in caf1Δdcr1Δ cells at tlh (Supplemental Fig.…”
Section: Absence Of Rna Degradation Leads To Changes In Chromatin Orgmentioning
confidence: 93%
“…Wang et al, 2012). Active Aurora B then phosphorylates Ser-10 of histone H3 (H3S10ph), which affects chromosome condensation and segregation (Yamagishi et al, 2010;Castellano-Pozo et al, 2013). A recent study reported that a mutation in the Arabidopsis thaliana Aurora1 gene results in a defect in meiotic chromosome segregation (Demidov et al, 2014), but the cellular defects of the aberrant meiosis were not described in detail.…”
Section: Introductionmentioning
confidence: 99%
“…R loops form when an RNA molecule anneals to a homologous DNA sequence in the genome, generating a region of DNA:RNA hybrid and a displaced ssDNA. R loops can act as precursors to genomic instability, modulators of gene expression, and regulators of chromatin epigenetic marks (Huertas and Aguilera 2003;Li and Manley 2005;Nakama et al 2012;Castellano-Pozo et al 2013;Sun et al 2013;Wahba et al 2013). Given the centrality of R loops in many genomic functions, the precise mapping of where they form and understanding why they form are important biological questions.…”
mentioning
confidence: 99%